Infección por el virus de la hepatitis A: epidemiología y diversidad genética (2015)
ABSTRACT: Hepatitis A virus infection is a global public health problem. The virus has a wide range of distribution and it is the main cause of acute hepatitis transmitted by the enteric route in Latin America. The viral particle is stable under environmental conditions and conserves its infectivity for several weeks, enabling its transmission by contaminated water and food. Worldwide, different epidemiological patterns have been identified, which may change over time by modification of social and economic variables in the population such as vaccination and the improvement of hygiene and primary health conditions. This leaves new populations susceptible to infection. In Latin America the circulation of genotype I and subgenotypes A and B has been described, but more research is needed to provide the knowledge needed to manage the prevention and control plans for the worldwide reduction of the prevalence of infection. For this paper, a literature review was performed on the SciELO, PubMed and ScienceDirect databases under the search terms "Hepatitis A", "Epidemiology," "Seroprevalence" and "Infection." From the results obtained, only papers published in English and Spanish to describe epidemiological and molecular studies of interest in Latin America were included. Key words: Epidemiologia, Hepatite, Saúde Pública, Vírus da Hepatite A.